Is it possible to decontaminate N95 masks in pandemic times? integrative literature review - Oliveira, Adriana Cristina de (2020)
ABSTRACTObjective: To evaluate the protocols on decontamination/reuse of N95 masks available in the literature in times of the Covid-19 pandemic.Method: Integrative literature review, in the period from 2010 to 2020, on the databases MEDLINE/PubMed, Science Direct, Cochrane, SAGE journals,Web of Science, Scopus, Embase and Wiley, with the descriptors Masks AND Respiratory protective devices; Mask OR N95 AND Covid-19; N95 AND Respirators; Decontamination AND N95 AND Coronavirus; Facemask OR Pandemic.Results: Twelve studies were included, of which 3 (30.0%) used ultraviolet germicidal irradiation and indicated mask deterioration between 2 and 10 cycles, 4 (40.0%) used hydrogen peroxide vapor, and seal loss varied from 5 to 20 cycles, 4 (33.3%) evaluated the structural integrity of the N95 mask through visual inspection and 6 (54.4%), its filtration efficiency.Conclusion: Reuse strategies to overcome a shortage of devices in the face of the pandemic challenge the current concept for good practices in health-product processing. Keywords: Masks. Respiratory protective devices. Decontamination. Coronavirus. Coronavirus infections. Pandemics.